An Overview of Various Classification Concepts of Web Page Content - Khan, R; Gupta, RK; Namdeo, V (International Journal of Computer Sciences and Engineering, 2019)
This paper collects the information about contents available over webpage since the Web is a huge stock of information that requires precise automated classifiers for web pages to manage web directories and increase search engine performance. In the Web page classification problem, each term can be used as a feature of each HTML / XML tag of each web page. This is an efficient way to select the best features to reduce the functional space of the derived Web page classification problem here. Content classification of web pages is essential for many Web information retrieval tasks, such as web directory management and targeted scanning. The uncontrolled nature of web content poses additional problems for the classification of web pages over traditional text classification. However, the interdependent nature of hypertext also provides functions that support the process. As with the work described in the Web page classification, the meaning of these Web-specific functions and algorithms describes leading practices and follows the assumptions underlying the use of adjacent page information.